The role of ferric coagulant on gypsum scaling and ion interception efficiency in nanofiltration at different pH values: Performance and mechanism. (15th May 2020) - Lin, Dachao; Bai, Langming; Gan, Zhendong; Zhao, Jing; Li, Guibai; Aminabhavi, Tejraj M.; Liang, Heng
Abstract: Nanofiltration (NF) is extensively applied after coagulation, which is conducive to alleviate organic fouling on NF membranes and improve water purification performance. However, inorganic fouling, which remains the major obstacle to limit the wider application of NF, could be enhanced by even low dosage coagulant. Few researchers realize the existence of coagulant-enhanced scaling, much less control it. This study investigated the effects of pH values on ferric-coagulant-influenced membrane performance during the nanofiltration of brackish water. Both membrane flux behavior (initial membrane flux, normalized flux during filtration, scaling resistance and scaling composition) and ion interception (filtrate conductivity and ions removal) were considered. Solution properties (zeta potential and nanoparticle size) were measured, and coagulant speciation variation was stimulated by Visual MINTEQ software. Mechanisms of ferric-coagulant-influenced membrane performance were analyzed from two aspects on the basis of correlation analyses: interface interaction on membrane surface and salts crystallization process (bulk crystallization and surface crystallization). Results showed that both bulk crystallization in feed solution and surface crystallization on membrane surface were dramatically induced by coagulant. Coagulant-enhanced fouling layer resistance decreased after the initial increase when pH varied from 3.0 to 10.0. Fe(OH)3, a kind of active ingredients in ferric coagulant, was highly responsible for the enhanced scaling layer resistance. Coagulant was found improving ionic removal under acidic conditions despite the fact that it could worsen removal under alkaline conditions. This study is of valuable reference to figure out the mechanisms of coagulant-influenced membrane performance and find a feasible approach to avoid membrane deterioration in coagulant-influenced NF process. Graphical abstract: Image 1 Highlights: The role of coagulant on membrane performance in nanofiltration at different pH was investigated. Ferric coagulant could dramatically enhance bulk crystallization and surface crystallization in nanofiltration. The deteriorated interception capacity by alkalization in nanofiltration was further aggravated by coagulant. Acidification could alleviate membrane fouling and allow coagulant to strengthen ionic rejection in nanofiltration. The mechanisms of coagulant-influenced membrane performance were proposed.